Developments in Danish research performance: Scientometric mapping of developments in Danish research performance in the period 1980-2013 at macro- and meso-levels - Aagaard, Kaare; Schneider, Jesper Wiborg (CFA Scientific Reports, 2015)
Based on a study commissioned by The Danish Council for Research and Innovation Policy (DFiR) this report examines the relationship between research policy and research performance in a long term perspective. The study takes its departure from six hypotheses formulated by DFiR related to research funding balances, excellence schemes, PhD education, governance structures and collaboration (international as well as cross sectoral). A cross-country comparison between Denmark, The Netherlands and Sweden serves to examine the links between such policy changes and aggregated academic impact in different national settings. By providing an improved understanding of the foundation for sustained high systemic research performance across countries the study thus aims to strengthen the foundation for future research policy decisions.